La teatralización de la violencia y la complicidad del espectáculo en Información para extranjeros de Griselda Gambaro - Cortés, Jason (Latin American Theatre Review, 2001)
This study examines the use of violence within the theatrical space of Griselda Gambaro’s Información para extranjeros. The play exhibits an eradication of the existing boundaries between victim and assailant, between spectator and torturer, as violence becomes a spectacle. In this manner, an inversion or substitution takes place evidencing the complicity between the spectator/reader and the torturer/playwright, and laying bare the capacity within us to exert violence against the Other. This inversion becomes disturbing for the spectator, who realizes the ubiquitous nature of violence, and the apparent impossibility of its avoidance. Thus, Gambaro seems to propose a paradox that is as overwhelming as the text that portrays it: violence can only be deterred through knowledge, however, this knowledge implies being victimized, and sometimes, becoming an accomplice. This paradox of knowledge and complicity is also analyzed in Julio Cortázar’s short story "Press Clippings." Information for Foreigners as well as "Press Clippings" explore the nature of violence, its relation to knowledge and its consequences over the reader and the spectator. (JC, in Spanish)